Post-exposure prophylaxis in the era of pre-exposure prophylaxis: a study of post-exposure prophylaxis use in South-East Queensland since the Pharmaceutical Benefits Scheme listing of pre-exposure prophylaxis. (April 2020) - Biggs, Karen; O'Sullivan, Maree; Palmer, Cheryn; McLellan, Jacqualine; Marple-Clark, Fiona; Spinks, Adam; Langton-Lockton, Julian; Thng, Caroline
Both post-exposure prophylaxis (PEP) and pre-exposure prophylaxis (PrEP) involve the use of antiretroviral drugs taken by HIV-uninfected individuals to reduce HIV acquisition risk. While PEP has been available in Australia for many years, PrEP became widely accessible in 2018 after listing on the Pharmaceutical Benefits Scheme (PBS). Studies have reported on the impact of PrEP on condom use. The impact of PrEP on the use of PEP in Australia has not been reported. This project examined PEP use across three public sexual health services in South-East Queensland, Australia, comparing rates in 2016 (prePBS-listed PrEP) and 2019 (postPBS-listed PrEP), to determine if PEP prescribing, and the characteristics of people accessing PEP, have changed. Results showed that PEP prescribing made up 2.85% of all clients seen in 2016, dropping to 2.33% in 2019, reflecting a decrease of 0.5% (p = 0.048). There was a significant increase in Medicare-ineligible clients accessing PEP (9% in 2016; 21% in 2019; p = 0.002) and a significant increase in PrEP-experienced clients accessing PEP between the two study periods (4% in 2016; 14% in 2019; p ≤ 0.001). The marginal decrease in PEP prescribing highlights that PEP remains an important option especially for those with barriers to accessing and adhering to daily PrEP.